The Role of Omentin-1 and Fibroblast Growth Factor-23 in Iraqi Patients with Prostate Cancer during Chemotherapy - Al-qazzaz, Ammar; Altaie, Anwar F. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Omentin-1 is mainly expressed in stromal vascular cells of adipose tissue and can also be expressed in airway goblet cells, mesothelial cells, and vascular cells. Fibroblast growth factor 23 (FGF-23), generated by bone cells, regulates phosphate and vitamin D metabolism by regulating phosphate reabsorption in the kidneys and inhibiting vitamin D activation. Vitamin D is a fat-soluble vitamin that regulates calcium absorption, bone health, and immunological function. Prostate cancer is a significant health concern for men worldwide. Several studies demonstrated a link between these variables and cancer as they exert important anti-inflammatory, antioxidative, and anti-cancer functions.  Objectives: To assess the impact of Omentin and FGF-23 biochemical functions, as well as the anti-cancer properties of vitamin D. Subjects and methods: This is a case-control study on serum samples collected from Iraqi prostate cancer patients after receiving chemotherapy at Al Amal Center in Imam Hussein Medical City in Karbala between November 2022 to May 2023. The serum samples were collected from two groups:  control group consisted of 30 healthy males. Patient group consisted of 30 prostate cancer patients after receiving chemotherapy, both groups aged 45 – 80 years. The two groups were matched for body mass index. ELISA technology was used to estimate serum levels of the aforementioned biochemical parameters with vitamin D. Results: patient group had a significantly higher FGF-23 level than control group (309.5±41.65) versus (163.1±22.4) (p